Highly economical and direct amination of sp3 carbon using low-cost nickel pincer catalyst. Issue 3 (6th January 2021) - Brandt, Andrew; RanguMagar, Ambar B.; Szwedo, Peter; Wayland, Hunter A.; Parnell, Charlette M.; Munshi, Pradip; Ghosh, Anindya
Abstract : Developing more efficient routes to achieve efficient C–N bond coupling is of great importance to industries ranging from products in pharmaceuticals and fertilizers to biomedical technologies and next-generation electroactive materials. Abstract : Developing more efficient routes to achieve C–N bond coupling is of great importance to industries ranging from products in pharmaceuticals and fertilizers to biomedical technologies and next-generation electroactive materials. Over the past decade, improvements in catalyst design have moved synthesis away from expensive metals to newer inexpensive C–N cross-coupling approaches via direct amine alkylation. For the first time, we report the use of an amide-based nickel pincer catalyst (1 ) for direct alkylation of amines via activation of sp 3 C–H bonds. The reaction was accomplished using a 0.2 mol% catalyst and no additional activating agents other than the base. Upon optimization, it was determined that the ideal reaction conditions involved solvent dimethyl sulfoxide at 110 °C for 3 h. The catalyst demonstrated excellent reactivity in the formation of various imines, intramolecularly cyclized amines, and substituted amines with a turnover number (TON) as high as 183. Depending on the base used for the reaction and the starting amines, the catalyst demonstrated high selectivity towards the product formation. The exploration into the mechanism and kinetics of the reaction pathway suggested the C–H activation as the rate-limiting step, with the reaction second-order overall, holding first-order behavior towards the catalyst and toluene substrate.